2016
DOI: 10.1039/c5cs00682a
|View full text |Cite
|
Sign up to set email alerts
|

Recent highlights in mixed-coordinate oligophosphorus chemistry

Abstract: This review aims to highlight and comprehensively summarize recent developments in the field of mixed-coordinate phosphorus chemistry. Particular attention is focused on the synthetic approaches to compounds containing at least two directly bonded phosphorus atoms in different coordination environments and their unexpected properties that are derived from spectroscopic and crystallographic data. Novel substance classes are discussed in order to supplement previous reviews about mixed-coordinate phosphorus comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
42
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 281 publications
(107 reference statements)
1
42
0
Order By: Relevance
“…Indeed, DFT calculations on the truncated model complex [Cp Ph Co{h 4 -P 5 iPr 2 (X)}] 2' '-X-iPr (X = Cl and Cy; Cp Ph = C 5 (C 6 H 5 ) 5 ,P BE/def2-TZVP level, see the Supporting Information for further details) gave several low-energy isomers,w hich likely form an equilibrium in solution (see Scheme 3). Thep entaphosphorus ligand is clearly h 3 -coordinated (Co1-P2 2.2831 (12) ,C o1-P4 2.2648(11) ,a nd Co1-P5 2.3152 (11) )and shows aboat conformation as aresult. Theexperimental 31 P{ 1 H} NMR spectrum of 2-Cl-iPr ( Figure S92) shows as econd isomer (AEMXY spin system) below À70 8 8C, which could correspond to 2-Cl-iPr-B or 2-Cl-iPr-C. [33] Initial attempts toward the organofunctionalization of 2-R[BArF 24 ]w ith CyMgCl led to ap roduct mixture (Figure S83) with [Cp Ar Co{h 3 -P 5 iPr 2 (Cy)}] (2-Cy-iPr)asthe major species,showing an AEMXY spin system.…”
Section: Forschungsartikelmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, DFT calculations on the truncated model complex [Cp Ph Co{h 4 -P 5 iPr 2 (X)}] 2' '-X-iPr (X = Cl and Cy; Cp Ph = C 5 (C 6 H 5 ) 5 ,P BE/def2-TZVP level, see the Supporting Information for further details) gave several low-energy isomers,w hich likely form an equilibrium in solution (see Scheme 3). Thep entaphosphorus ligand is clearly h 3 -coordinated (Co1-P2 2.2831 (12) ,C o1-P4 2.2648(11) ,a nd Co1-P5 2.3152 (11) )and shows aboat conformation as aresult. Theexperimental 31 P{ 1 H} NMR spectrum of 2-Cl-iPr ( Figure S92) shows as econd isomer (AEMXY spin system) below À70 8 8C, which could correspond to 2-Cl-iPr-B or 2-Cl-iPr-C. [33] Initial attempts toward the organofunctionalization of 2-R[BArF 24 ]w ith CyMgCl led to ap roduct mixture (Figure S83) with [Cp Ar Co{h 3 -P 5 iPr 2 (Cy)}] (2-Cy-iPr)asthe major species,showing an AEMXY spin system.…”
Section: Forschungsartikelmentioning
confidence: 99%
“…[27] Thec ore of the structure is an unsymmetrical, exo,exo-substituted P 4 "butterfly" unit, showing as imilar folding (P2···P4 2.8047-(10) )a so ther exo,exo-substituted bicyclo-[1.1.0]tetraphosphanes. [28] As ac onsequence,t he bridgehead P3ÀP5 bond (2.1764(11) )isshorter than the remaining PÀP bonds (2.2104(11)-2.2299 (12) ). The 31 P{ 1 H} NMR spectrum of 1-iPr·GaCl 3 recorded in C 6 D 6 (see the Supporting Information, Figure S8) is in agreement with the molecular structure (AMXY 2 spin system; d = 16.4, À107.3, À267.6, and À324.2 ppm).…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Computational calculations suggested that the P2 atom is the preferred reaction site towards nucleophiles . This is experimentally illustrated by the outcome of the reaction of 65 + with the Lewis base PMe 3 , giving the unique cation 66 + as the GaCl 4 − salt, which features a unique example of a phosphane environment that bridges a phosphanide and a phosphonium moiety . Diphosphene 65 [OTf] reacts with aryl‐substituted azides of type R‐N 3 (R=Dipp or Dmp (2,5‐dimethylphenyl)) by a [2+3] cycloaddition reaction followed by the release of N 2 and a subsequent electrocyclic ring‐closing reaction to azadiphosphiridine salts 67 a , b [OTf] (Scheme , right) .…”
Section: Imidazoliumyl‐substituted Phosphorus Compoundsmentioning
confidence: 99%
“…[57] This is experimentally illustrated by the outcomeo ft he reaction of 65 + with the Lewis base PMe 3 ,g iving the unique cation 66 + as the GaCl 4 À salt, which features au nique example of ap hosphane environmentt hat bridges ap hosphanide and ap hosphonium moiety. [59] Diphosphene 65[OTf]r eacts with aryl-substituted azides of type R-N 3 (R = Dipp or Dmp (2,5-dimethylphenyl)) by a[ 2 + +3] cycloaddition reaction followed by the release of N 2 and as ubsequente lectrocyclic ring-closing reaction to azadiphosphiridine salts 67 a,b[OTf] (Scheme 18, Scheme16 right). [60] The 31 Pc hemical shifts and the comparatively small 1 J PP coupling constants of 67 a,b + (67 a + : d(P A ) = À104.8 ppm, d(P X ) = À49.9 ppm, 1 J PP = À122 Hz; 67 b + : d(P A ) = À107.5 ppm, d(P X ) = À58.1 ppm, 1 J PP = À131 Hz) are well in the range for those observedf or neutral azadiphosphiridines.…”
Section: Scheme11mentioning
confidence: 99%